Acute endurance exercise lowers serum fibroblast growth factor 21 levels in Japanese men. (23rd August 2016) - Taniguchi, Hirokazu; Tanisawa, Kumpei; Sun, Xiaomin; Higuchi, Mitsuru
Summary: Objective: The independent effects of acute endurance exercise on FGF21 metabolism are poorly understood. Therefore, the purpose of this study was to determine whether acute endurance exercise modulates serum postprandial FGF21 levels in an age‐dependent manner. Design: Exercise intervention trial. Patients: Twenty‐eight subjects participated in the experiment, of whom 13 were excluded mainly because of a serum FGF21 level below the limit of detection. Thus, data from seven young (age: 18–22 years) and eight elderly male subjects (age: 62–69 years) were analysed. Measurements: Participants were asked to perform a cycling exercise for 30 min at 70% maximal oxygen uptake, following carbohydrate intake. Blood samples were collected pre‐exercise and 0 min, 30 min, 1 h, 3 h and 24 h after the cessation of exercise. Serum FGF21 levels were measured by an enzyme‐linked immunosorbent assay. Results: Higher serum FGF21 was observed in the elderly subjects group throughout the experiment ( P < 0·05). There was no significant increase in serum FGF21 levels after the cessation of exercise, whereas serum FGF21 levels were significantly lower 24 h after the exercise compared with those pre‐exercise, 0 min, 30 min and 1 h after the cessation of exercise in both groups ( P < 0·01). The response did not differ between the two groups because of no significant group × time interaction. Conclusions: Acute endurance exercise lowers serum FGF21 levels 24 h following exercise. The results suggest that acute endurance exercise modulates postprandial FGF21 metabolism regardless of age.